Some aspects of cool main sequence star ages derived from stellar rotation (gyrochronology). Issue 8 (30th September 2016) - Barnes, S. A.; Spada, F.; Weingrill, J.
Abstract: Rotation periods for cool stars can be measured with good precision by monitoring starspot light modulation. Observations have shown that the rotation periods of dwarf stars of roughly solar metallicity have such systematic dependencies on stellar age and mass that they can be used to derive reliable ages, a procedure called gyrochronology. We review the method and show illustrative cases, including recent ground‐ and space‐based data. The age uncertainties approach 10 % in the best cases, making them a valuable complement to, and constraint on, asteroseismic or other ages.